L’historien et le jeu-vidéo - Julien Lalu (Conserveries Mémorielles)
When they speak about historical representations in video games, it’s often thought of war and, whatever is the type of game. This omnipresence reinforces idea that past was built by war. However, besides this warlike aspect which seems to be a play marker the developers who use past are possible have also an educational or patrimonial aim. It’s the case of the ludo-educational or ludo-cultural software which develops from 1990’s. In it, the creators try to find a balance within software between play aspect and educational contribution. By exceeding semantic debate enter narratology and ludology, it’s necessary to analyse game and its representations both by prism of the gameplay and of the mechanics of game by that of narration and way these representations are staged to include as past can be represented in the particular frame of video game. Leaving this postulate, this article has two objectives. Offer a historical step of analysis of the object-game to grab in what the historian can use this medium to understand stakes of the representations of past in popular culture. And take a example of Versailles 1685 : complot à la cour du roi soleil to include how the play, cultural and pedagogic aspects can co-exist in a game without denaturing it.